Faster leaf senescence after flowering in wet direct‐seeded rice was mainly regulated by decrease in cytokinin content as compared with transplanted‐flooded rice - Hongyan Liu (Food and Energy Security, 2020)
Abstract Wet direct‐seeded rice (WDSR) is considered as a practicable substitute to transplanted‐flooded rice (TFR) because it copes with labor and water shortages, and reduces greenhouse gas emissions. However, the differences between WDSR and TFR in leaf senescence after flowering and the associated mechanisms have rarely been identified. In this study, the growth dynamics, SPAD value of flag leaf, dry matter accumulation and translocation, and the contents of plant hormones (ABA, CTKs, and GA3) in WDSR and TFR rice flag leaves after flowering were compared during the rice‐growing seasons of 2013, 2014, and 2018. The results showed that leaf senescence after flowering in WDSR was faster in comparison with TFR. The amount of dry matter acquired after flowering (ΔW) in WDSR was significantly lower and might be related to the faster leaf senescence after flowering in WDSR compared with TFR. The CTK content in flag leaves after flowering was lower in WDSR than in TFR, and CTK content declined earlier than SPAD value, which implied that decrease in CTK content could be a possible reason for the early leaf senescence in WDSR. In conclusion, faster leaf senescence after flowering in WDSR was mainly attributed to the decline in leaf CTK content.